Management Strategies for Developing the PAI Learning Program at SMP NU Islamic Center Pesanggaran - Andry Arifianto; Galuh Prabowo; Andi Setiawan; Zohaib Hassan Sain; Hafidhur Rohman Saad Robbani; Zulfa Duerapho (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
The purpose of this study was to analyze the management of the development of Islamic Religious Education learning programs at SMP NU, focusing on the approaches applied in curriculum planning, teacher competency development, and the implementation of applicable religious activities. This study uses a qualitative approach with a case study design to analyze the management of the development of Islamic Religious Education learning programs at SMP NU Al-Islami Pesanggaran. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis was carried out by identifying the main themes, such as curriculum planning and teacher competency development. Data validity was maintained through source triangulation and member checks. The results of this study confirm that adaptive and relevant curriculum planning is very important to meet student needs and developments. The curriculum must consider student characteristics and integrate character values in learning. The development of Islamic Religious Education teacher competencies is also a major factor in improving the quality of education, especially through routine training and the application of interactive methods. Continuous evaluation and supervision, including principal supervision and analysis of learning outcomes, play a role in improving the effectiveness of teaching. These findings are in line with constructivism theory and clinical supervision which emphasize active, reflective, and collaboration-based learning. Thus, an adaptive curriculum approach, improving teacher competency, and ongoing evaluation are effective strategies in improving the quality of education as a whole.